Maximizing performance in child footballers: chronotype and time of day study - Kaba, Ilknur; Engin Celikel, Baha; Adanur, Oguzhan; Yilmaz, Coskun; Yonca Sezer, Sureyya; Tan, Cetin; Ceylan, Tulay (Frontiers Media Sa, 2025)
Background A limited number of studies have investigated the effects of circadian rhythm-based running exercise interventions on physical fitness in child athletes. This study aimed to investigate the effects of an eight-week morning and evening running program on lower extremity strength, agility and respiratory function in 10-12-year-old male footballers.Methods Participants visited the laboratory three times, with one-day intervals before and after the training program. The assessments included maximal inspiratory pressure (MIP), maximal expiratory pressure (MEP), forced expiratory volume in one second (FEV1), forced vital capacity (FVC), and the FEV1/FVC ratio. Additionally, agility and functional performance tests (FPTs) were conducted for both the dominant and non-dominant legs.Results The findings indicated that morning running was more effective than evening running in enhancing respiratory function. Morning running also showed superior results in lower extremity strength tests, particularly in the single-leg (SL) and triple-leg (THD) crossover hop for distance tests (CHDs) and the 6-m timed-hop test (6 m THT). Furthermore, the agility performance of the morning running group was significantly better than that of the evening and control groups.Conclusion Consequently, morning running interventions had a positive impact on key physical fitness parameters, including respiratory muscle strength, respiratory function, agility, and lower extremity strength in child footballers.
Keywords: physical fitness; children's health; respiratory function; exercise interventions; circadian rhythm; chronotype